Analisis Perbandingan Kinerja Keuangan PT. Bank NTB Syariah Kantor Pusat Dengan Menggunakan Metode RGEC Pada Masa Transisi Dan Setelah Terkonversi Menjadi Bank Umum Syariah - Sufiana Pujiarti; Lalu Hamdani Husnan; Embun Suryani (Journal of Management and Creative Business, 2023)
This study is entitled analysis of the financial performance of PT Bank NTB Syariah head office using the RGEC method during the transition period and after being converted into an Islamic commercial bank. Aims to determine the significance level of Islamic NTB bank performance using the RGEC method during the transition period and after conversion. The type of research used is descriptive research with a quantitative approach. The data collection method used is the method of documentation and literature study. The population in this study were financial statements, GCG reports of head office Islamic NTB banks and the samples were NPF/NPL, FDR/LDR, ROA, ROE, BOPO, NI, CAR and PDN ratios. The analysis tool used is the Wilxocon signed rank test using SPSS version 17. The results of the analysis show that: (1) financial performance during the transition period using the RGREC method gets a composite value of 1 or very healthy (2) financial performance after being converted using the RGEC method gets a composite value 1 or very healthy (3) the comparison of financial performance during the transition period and after conversion is not too significant.